The assessment of organizational culture in cross‐cultural settings: Investigating the psychometric quality and cultural equivalence of three quantitative instruments. (March 2017) - Puppatz, Martin; Burmeister, Anne; Deller, Juergen
Abstract: This study tested the psychometric quality and cultural equivalence of the German versions of three instruments for measuring organizational culture: the Denison Organizational Culture Survey (DOCS), the Organizational Culture Profile (OCP), and the Global leadership & organizational behavior effectiveness survey (GLOBE). Using an organizational sample from the banking industry, we analyzed the metric equivalence (by means of assessing the psychometric quality), the conceptual equivalence (by means of assessing the construct validity) as well as the linguistic and functional equivalence of the three instruments. The results indicate that the psychometric properties and the equivalence of the DOCS and the OCP can be summarized as satisfactory. In contrast, reliability indices of the GLOBE scales were far below recommended thresholds and results regarding its construct validity were unsatisfying. Conceptual equivalence could therefore not be assumed. Avenues for future research and implications for practitioners are discussed. In addition, the authors created and tested a German translation of the OCP scales and an adapted version of the German DOCS scales.